Low-dose aspirin for the prevention of preeclampsia in women with polycystic ovary syndrome: a retrospective cohort study - Shouling Luo; Xiaoyue Zhang; Zhenzhen Liu; Chengjie Wang; Jiangnan Pei; Yi Yu; Haiyan Liu; Weirong Gu (BMC Pregnancy and Childbirth)
Abstract Background The objective of this study was to investigate the efficacy of low-dose aspirin (LDA) in preventing preeclampsia among pregnant women with polycystic ovary syndrome (PCOS), given the increased susceptibility of this population to preeclampsia development. Methods A retrospective cohort study was conducted on pregnant women with PCOS who delivered between January 1, 2018 and February 10, 2024 at our institution. Clinical characteristics and obstetric data were extracted from medical records. Propensity score matching (PSM) was employed to analyze the association between LDA use and PE incidence. Results The study cohort comprised 1522 pregnant women with PCOS. Among 395 pregnant women identified as high-risk for preeclampsia, 98 were administered LDA for preeclampsia prevention, while 297 did not receive LDA. Following PSM, no statistically significant difference was observed in preeclampsia risk between the LDA and non-LDA groups. Additionally, maternal and neonatal outcomes were comparable between the two groups. Conclusions This cohort analysis did not provide sufficient evidence to support the efficacy of LDA in preventing preeclampsia among PCOS patients at high risk for preeclampsia.